2016
DOI: 10.3390/rs8060497
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Black Lakes and Using 810 nm Reflectance Peak for Retrieving Water Quality Parameters of Optically Complex Waters

Abstract: Many lakes in boreal and arctic regions have high concentrations of CDOM (coloured dissolved organic matter). Remote sensing of such lakes is complicated due to very low water leaving signals. There are extreme (black) lakes where the water reflectance values are negligible in almost entire visible part of spectrum (400-700 nm) due to the absorption by CDOM. In these lakes, the only water-leaving signal detectable by remote sensing sensors occurs as two peaks-near 710 nm and 810 nm. The first peak has been wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 44 publications
7
92
0
1
Order By: Relevance
“…The best calibration and validation results obtained by Sentinel 2 MSI B7 (centered at 783 nm) may be explained by the fact that it lies in the left shoulder of the SPM reflectance peak around 810 nm (Figure 2a), which is a result of particulate backscattering and slight decrease in water absorption [51]. Such a result is consistent with that of Kutser et al [23], who demonstrated the capability of Sentinel 2 MSI B7 in retrieving C SPM values over strong absorbing black waters due to its adjacency to 810 reflectance peak.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The best calibration and validation results obtained by Sentinel 2 MSI B7 (centered at 783 nm) may be explained by the fact that it lies in the left shoulder of the SPM reflectance peak around 810 nm (Figure 2a), which is a result of particulate backscattering and slight decrease in water absorption [51]. Such a result is consistent with that of Kutser et al [23], who demonstrated the capability of Sentinel 2 MSI B7 in retrieving C SPM values over strong absorbing black waters due to its adjacency to 810 reflectance peak.…”
Section: Discussionsupporting
confidence: 80%
“…The absorptions of the optically active matters could still contribute to the reflectance of Sentinel 2 MSI B4 (centered at 665 nm), especially for waters with high loading of SPM or the presence of absorbing substances [3,23]. Therefore, the relationships between C SPM and R rs at this band are complicated, and the calibration samples scattered sparsely around the fitting curve in Figure 3, which explains the relatively lower performance obtained by Sentinel 2 MSI B4.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, estimating only turbidity by using a near-infrared wavelength of about 740 nm or more, which is hardly affected by Chla absorption, can be considered appropriate as seen in Figure 1. In contrast, Kutser et al [29] used bands of 770 nm, 810 nm and 840 nm (T3 model of this study), proposing a new 3-BM targeting the peak near 810 nm in CDOM-rich water areas. This method originally estimates the 810-nm height using the average height of 770 nm and 840 nm as a baseline.…”
Section: Evaluation Of Turbidity Algorithmmentioning
confidence: 99%
“…Furthermore, in waters with a large CDOM influence, a 3-BM (hereinafter referred to as the T3 model) [29] with a high R rs of 810 nm as an index has recently been proposed.…”
Section: Chlorophyll-a and Turbidity Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation